2020
DOI: 10.1002/aocs.12377
|View full text |Cite
|
Sign up to set email alerts
|

Development of Industrially Scalable Method for Phospholipids and Branch‐Chain Fatty Acids of Dairy by‐Product

Abstract: Dairy phospholipids (PL) is of interest due to their health benefits and functional properties. Solvent fractionation of PL has not been commonly used in the dairy industry to fractionate milk fat to obtain or concentrate the PL. The total lipid extracted from the β stream, a waste by‐product of dairy processing, was used in this study to investigate suitable solvent and conditions to separate the neutral lipid from PL. A fixed lipid solvent ratio (1:10 g/v) was used at various fractionation temperatures (−20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In contrast, Ahmed et al (2015) found higher contact angle values ~ 95° after 5 s for a concentration of 0.11 mg/cm 2 of brace roots of five-week-old maize plant. Incomplete removal of phospholipids upon EtOH precipitation (Price et al 2020) does not explain the increase of the contact angle after purification, which contradicts hypothesis 3. One chemical explanation for the appearance of hydrophobic regions in dry mucilage in general suggests an amphiphilic nature of the polymers and a reorientation of amphiphilic molecules such as proteins, or flexible hydrophilic and hydrophobic moieties.…”
Section: Effect Of Treatment On Wettabilitymentioning
confidence: 80%
“…In contrast, Ahmed et al (2015) found higher contact angle values ~ 95° after 5 s for a concentration of 0.11 mg/cm 2 of brace roots of five-week-old maize plant. Incomplete removal of phospholipids upon EtOH precipitation (Price et al 2020) does not explain the increase of the contact angle after purification, which contradicts hypothesis 3. One chemical explanation for the appearance of hydrophobic regions in dry mucilage in general suggests an amphiphilic nature of the polymers and a reorientation of amphiphilic molecules such as proteins, or flexible hydrophilic and hydrophobic moieties.…”
Section: Effect Of Treatment On Wettabilitymentioning
confidence: 80%
“…Incomplete removal of phospholipids upon EtOH precipitation (Price et al, 2020) does not explain the increase of the contact angle after puri cation, which contradicts hypothesis 3. One chemical explanation for the appearance of hydrophobic regions in dry mucilage in general suggests an amphiphilic nature of the polymers and a reorientation of amphiphilic molecules.…”
Section: Effect Of Treatment On Wettabilitymentioning
confidence: 80%
“…The three organic phases collected were combined and dried to obtain the crude lipid extract. Then, 0.5 mL of precooled (-20 °C) acetone was added to the lipid mixture. , The mixture was vortexed for 60 s to mix thoroughly and was put in ice water ultrasonically for 10 min before being centrifuged at 10,000 rpm for 10 min at 2 °C. Next, the supernatant was removed, and the above steps were repeated two times.…”
Section: Methodsmentioning
confidence: 99%